2012
DOI: 10.1016/j.wear.2012.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature and crystal orientation on tool wear during single point diamond turning of silicon

Abstract: Owing to the capricious wear of cutting tools, ultra precision manufacturing of silicon through single point diamond turning (SPDT) operation becomes a challenging task. It thus becomes non-trivial to understand the contribution of temperature and crystal orientation during the SPDT process in order to suppress tool wear. Molecular dynamics (MD) simulation is an appropriate tool to study nanoscale processes occurring at the femtosecond/picosecond timescale which cannot otherwise be studied experimentally or by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(43 citation statements)
references
References 36 publications
0
43
0
Order By: Relevance
“…The implication of this phenomenon is that a more negative inclined tool edge (rake angle) will result in deeper sub-surface damage caused by the formation of such periodically appearing cavities. Notably, the authors have tested several other potential functions under similar conditions [45,46], and it was found that such periodical grooves, which are known from cutting experiments, occur only with the screened empirical bond-order potential. This is a clear indication that the long-ranged screening function applied to the potential helps reproduce the brittle formation of surface cracks correctly.…”
Section: Surface Generation Process and Brittle Fracturementioning
confidence: 99%
“…The implication of this phenomenon is that a more negative inclined tool edge (rake angle) will result in deeper sub-surface damage caused by the formation of such periodically appearing cavities. Notably, the authors have tested several other potential functions under similar conditions [45,46], and it was found that such periodical grooves, which are known from cutting experiments, occur only with the screened empirical bond-order potential. This is a clear indication that the long-ranged screening function applied to the potential helps reproduce the brittle formation of surface cracks correctly.…”
Section: Surface Generation Process and Brittle Fracturementioning
confidence: 99%
“…Analytical bond order potential (ABOP) and reactive empirical bond order (REBO) potential functions were used to describe the covalent descriptions of silicon and carbon respectively [12]. The algorithm followed in this work is the same as has been used in the previous investigations [6,[13][14]. Additionally, an automated Dislocation Extraction Algorithm (DXA) [15][16][17][18] was also used to visualize and analyze the atomistic simulation data to identify dislocation lines.…”
Section: Modelmentioning
confidence: 99%
“…The accuracy of the potential function used in MD simulation determines the reliability of the simulation results [37]. Lennard-Jones (LJ), Morse and embeddedatom method (EAM) potentials were employed to investigate the effect of interaction potential on the MD simulation of nano-cutting by Oluwajobi et al [38].…”
Section: Methodsmentioning
confidence: 99%
“…Morse potential is usually used to depict the interaction between the atoms of cutting tool and workpiece materials. Goel et al [37] thought it is not robust enough to describe covalent bond interactions between silicon and diamond. Therefore, the analytical bond order potential (ABOP) proposed by Erhart and Albe [39] is used to describe the interaction within and between the diamond tool and silicon.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation